1987
DOI: 10.2527/jas1987.6551249x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Sows Fat or Fructose during Late Gestation and Lactation3

Abstract: The effects of dietary fat or fructose supplementation during late gestation and lactation on sow milk production and composition and on progeny were examined. On d 88 of gestation, 24 sows were allotted by parity to three dietary treatments (eight sows/treatment). Treatments were 1) a 12.5% crude protein, corn-soybean meal control, 2) the control + 10% added fat or 3) the control + 23% high fructose corn syrup. All treatments were fed to supply 1.82 kg/d of the control diet from d 89 of gestation to parturiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
1
15
1
Order By: Relevance
“…The effect of feeding high-fat diets to sows during lactation on the growth rate of newborn piglets is inconsistent. Some researchers have reported increased weanling weights in response to dietary fat levels (Boyd et al, 1982;Shurson et al, 1986), whereas others did not find this effect (Kruse et al 1977;Coffey et al, 1987). These discrepancies may be due to the variations in length of feeding supplemental fat, amount of fat in the feed and its source, and initial inclusion time.…”
Section: Introductionmentioning
confidence: 68%
“…The effect of feeding high-fat diets to sows during lactation on the growth rate of newborn piglets is inconsistent. Some researchers have reported increased weanling weights in response to dietary fat levels (Boyd et al, 1982;Shurson et al, 1986), whereas others did not find this effect (Kruse et al 1977;Coffey et al, 1987). These discrepancies may be due to the variations in length of feeding supplemental fat, amount of fat in the feed and its source, and initial inclusion time.…”
Section: Introductionmentioning
confidence: 68%
“…Energy needs for milk production are met through dietary energy and body tissue mobilization, therefore a lack of difference in body weight change for fructose-fed rats and reduced weaning weight of offspring suggests reduced milk production. Milk production and composition was not determined in response to fructose feeding in the present experiment however lactating multiparous sows fed fructose had reduced milk production and reduced milk fat percentage [49]. Therefore it is reasonable to assume that impaired growth in the suckling phase for offspring from fructose-fed rats is the result of a reduction in quantity of nutrients available from milk to support growth.…”
Section: Discussionmentioning
confidence: 92%
“…In this experiment, dietary inclusion of different glucose levels showed comparable litter performance of sows during lactation. Similarly, Coffey et al (1987) found that sows fed diet containing additional 23% high fructose corn syrup had similar litter performance as the control during lactation. van den Brand et al (2006) observed that addition of dextrose did not increase litter size, but seemed to increase the uniformity in birth weight of litter.…”
Section: Discussionmentioning
confidence: 74%
“…This might be explained that the energetic efficiency of milk synthesis from plasma glucose as precursors was high although the diets were isocaloric. However, Coffey et al (1987) found that the total lipid concentration was lower in sows fed fructose diet than that of control, whereas the milk production was comparable among the treatments. These discrepancies might be due to the differences in monosaccharide sources (glucose vs. fructose), amount or inclusive methods.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation